GC-MS and Phytochemical Analysis of Leaf Extract of Cassia Alata Used in the Treatment of Tinea Capitis - Folorunso, V. T. (British Journal of Healthcare and Medical Research, 2024)
Medicinal plants are rich source of bioactive phytochemicals Several thousands of plants species have been claimed to possess medicinal properties and employed in the treatment of many ailments. The study aimed to examine the bioactive compounds present in Cassia alata Linn as well as the physiochemical properties. Fresh leaves of cassia alata were collected from Akungba Akoko in Ondo State while the preparation of extract was also carried out. The analysis of Cassia alata leaf extract was performed using a gas chromatography – mass spectrometry (GC-MS QP2010 PLUS Shimadzu, Japan) techniques. GC-MS analysis of leaves of Casia alata ethanol extract showed the presence of components at the different retention time. The bioactive compound from GC-MS chromatogram of Casia alata showed at 48 peak with n-hexadecanoic acid and the molecular weight in gram was 256. 42g/mol while the retention time is at 14.801. The finding of this study provides an insight into the usage of these plants in traditional medicine for the treatment of common fungal infections. The bioactive compound present in ethanolic extract of the leaves of C. alata can contribute to the medicinal quality of the plant.